Analisis Financial Intelligence dalam menentukan keberhasilan usaha Koperasi serta dampaknya pada keunggulan bersaing berkelanjutan - Indra, Nurhayat; Arifin, Agus; Nuha, Maharayu Hawani (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The objective of this study is to determine the extent of the financial intelligence of the co-operation's success and the impact on the sustainable competition advantage of KUD Sarwa Mukti. The method used in this study is a quantitative descriptive method. Based on research it is known that the financial intelligence viewed by financial knowledge is conceptually good and provides economic benefits for members. As the financial industry as a whole, regulators and regulators are at the edge of uncertainty. The cooperatives' success perspectives, in the macro and micro-dimensions overall, are already good. Yet the volume of cooperative businesses tended to decline, the productivity of member enterprises was still low, and businesses, in the mako businesses were unable to provide economic benefits to members. On competitive advantage, kud sarwa mukti tends to excel over competitors. Financial intelligence officers and administrators have been implemented to determine the success of co-operation and to impact the sustainable competition advantage.